A critical analysis of the jurisprudence of the special court for Sierra Leone on the use of child soldiers - Kakungula-Mayambala, Ronald (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.